The Graphics of Initials and Capital Letters in Ruthenian Cursive Found in the Judicial Court Books of the Grand Duchy of Lithuania in the 17th Century - Diemantaitė, Vita (Lietuvos istorijos studijos, 2017)
In the Grand Dutchy of Lithuania, the main language was Ruthenian until 1697, when the main language became Polish. In Lithuanian historiography, the most developed researches concern the mental, ideological and social issues. These issues are discussed in the context of the first printed book, the first Lithuanian Statute, on the conduct of the first Lithuanian book, the first Lithuanian history problems. Ruthenian cursive is best examined in texts from the 16th century, in the First Lithuanian Statute and Lithuanian Metrics context. However, there are almost no studies about the Ruthenian cursive in 17th century. We haven’t investigated the individual pattern types or analyzed the letter graphics change, so, in general, the seventeenth century Ruthenian cursive is little explored. Therefore, this research focused on the initials and capital letters used in the Ruthenian cursive in the seventeenth century. We have chosen the most developed books of courts that have operated in the GDL in order to examine the changes of initials and capital letters during the 17th century. However, this article researches only the ethnographic territory of Lithuania, because of the availability of the books in the archive. The research proved that the graphics of capital letters changed very slowly and the difference is seen only from the middle of the seventeenth century. Initials were used to decorate the text very often and they depended on the individual scribe’s hand. The most frequently used initials were Г, Н, Л, П and Ѡ. In the seventeenth century, the most often used capital letters were А, В, К, Л, М, Н, П, Т, Ѡ. As the caps graphics changing gradually, the Latin alphabet options of M and N appeared in the 5th decade. Throughout the seventeenth century, letters В, Н and Ѡ have been changing the most, while the least changed letters were А, Л, М, П, Т.